Mechanistic exploration of obesity-related indicators and motor cognitive risk syndrome: a mediated effect based on C-reactive protein triglyceride glucose index - Guo, Zhongqiang; Deng, Shuang; Li, Li; Liu, Min (Frontiers in aging neuroscience, 2025)
To investigate the relationships between obesity-related indicators and motor cognitive risk syndrome (MCR), as well as the mediating role of the C-reactive protein triglyceride glucose index (CTI). The aim of this study was to provide evidence-based support to optimize MCR screening programs and develop prevention strategies for cognitive impairment in elderly individuals. This study utilized data from the China Health and Retirement Longitudinal Study (CHARLS) in 2015, and 5,665 participants were ultimately included. The independent variables were obesity-related indicators (WC, Waist circumference; WHtR, waist to height ratio; BRI, body roundness index; BMI, body mass index), and the mediating variable was CTI. Multiple logistic regression analysis, threshold effect analysis, and curve fitting analysis were used to analyze the relationships between obesity-related indicators and MCR. The mediation analysis method was used to observe the mediating effect of CTI. BMI, WC, WHtR, and BRI all significantly increased the risk of MCR. Threshold analysis revealed a nonlinear BRI-MCR association (inflection point = 2.45, = 0.041), whereas the association with WHtR was linear ( = 0.069). Mediation analysis revealed that the CTI mediated 20.99% of the effect of the WHtR on MCR, 25.55% of the effect of WC, and 21.74% of the effect of the BRI. The overall effect, direct effect, and indirect effect are all significant. This study, which is based on CHARLS data, revealed that obesity-related indicators (WC, WHtR, BRI) significantly correlate with MCR risk. Metabolic disorders mediate the association of WHtR with MCR, confirming their central role in the link between obesity and cognition. Threshold effects were observed. The proposed method is to incorporate WHtR and CTI into community health assessments for early cognitive impairment screening, offering evidence for targeted interventions in resource-limited settings.